The Relevance of Ki Hajar Dewantara's Educational Thought to the Curriculum 13 - Endang Trisiana (Beginner: Journal of Teaching and Education Management, 2023)
Education is the key to the development of the country. Ki Hajar Dewantara, an influential figure in education thinking in Indonesia, introduced the concept of "Taman Siswa" which is relevant to the principles of Curriculum 13, an effort to improve the quality of education. Dewantara emphasizes learner-focused education with a deep understanding of individual needs and potential, in line with the approach in Curriculum 13. In addition, Dewantara also highlighted character, moral, and nationalism education, in accordance with the objectives of Curriculum 13 to form learners who have strong character, integrity, and love for the state and nation. The purpose of the relevance of Ki Hajar Dewantara educational thinking to Curriculum 13 is to provide an understanding of the extent to which Dewantara thoughts and concepts in education can inform and support the principles and objectives of Curriculum 13, Explain the contribution of Ki Hajar Dewantara thought to the development of education.